(untitled) (Research, Society and Development, 2022)
This article aims to describe the effects of music therapy applied to children with complex chronic health conditions under the family member’s optics. Interventional and participatory research carried with eleven children with complex chronic health conditions from March to April 2021 in a medium-size city in the center-west of Brazil. Research was approved by the Research Ethics Committee under the protocol CAAE 41238820.1.0000.5595. According to the family members, there was a change of behavior during and after the music therapy sessions. Music therapy improved children’s communication, focus, interaction, relaxation and bond with the health professionals and family members.